Pengaruh Kecemasan AI terhadap Penggunaan AI Dimoderasi oleh Motivasi Belajar pada Mahasiswa FKIP UNS - Hanifa, Elisya Fachriana; Sudarno, Sudarno; Sabandi, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
AI Anxiety, AI Use, Motivation This study aims to analyze the effect of artificial intelligence (AI) anxiety on the use of AI technology with learning motivation as a moderating variable among Economics Education students at the Faculty of Teacher Training and Education, Sebelas Maret University. The study employed a descriptive quantitative approach with a sample of 70 students from the 2020 cohort, collected through a Likert scale questionnaire and analyzed using hierarchical regression with the assistance of SPSS 26. The results show that AI anxiety has a positive and significant effect on AI usage, indicating that the higher the level of student anxiety towards AI, the higher the intensity of AI usage as an adaptive strategy in completing academic tasks. However, learning motivation was not found to moderate the relationship between AI anxiety and AI usage, so that the effect of AI anxiety on AI usage remained consistent among students with different levels of learning motivation. These findings confirm that AI anxiety can function as a driver of adaptive behavior in the use of AI technology in higher education.